Uncertainty and the effectiveness of fiscal policy in the United States and Brazil : SVAR approach - Rodrigues, Eduardo de Sá Fortes Leitão (2020)
This paper analyses the harmful interference of uncertainty on the effectiveness of fiscal policy. We investigate this issue through the lens of a Structural Vector Auto Regressive (SVAR) model for the United States and Brazil. Imposing government spending shocks, we find a positive effect on economic activity. The results suggest Keynesian effects on consumption and GDP. To assess the effects of uncertainty, we used the Economic Policy Uncertainty Index (EPU) and the World Uncertainty Index (WUI). Our findings indicate that the fiscal effects are considerably less intense when uncertainty reaches high levels, consistently with the Real Options approach. The results suggest that agents are more cautious when the high uncertainty overshadows the outline of the economic scenario. In this sense, uncertainty disturbs agents’ decisions and decreases consumption, investment and economic activity.